Self Control in Savings (A Literature Review) - Eka Putri Suryantari; Gayatri Gayatri (Budapest International Research and Critics University, 2022)
The thing that is most feared by every individual is a situation of uncertainty that will occur in the future. Fear creates a sense of anxiety that will haunt every step the individual takes in navigating the ocean of his life. Uncertainty in financial conditions is one of the many uncertainties faced. Humans are born with various advantages in themselves compared to other living creatures created by God. With the mind that humans have, they try to find solutions to overcome problems, especially the fear of uncertainty, especially in financial matters. Along with the development of science, especially in the field of accounting, it teaches how to make a form of financial management, especially individual finance so that it can overcome problems in its finances. One way to manage finances is to save the money you have so that later it can be used for various predetermined purposes. Through the target to be achieved, the main focus that must be done is how to make every step taken in accordance with the objectives to be achieved. One of the things that supports the achievement of the targets to be achieved is the individual's commitment to carrying out all plans made through self-control which is reflected in his physical and behavior.